Involvement of GABAB receptors in biochemical alterations induced by anxiety-related responses to nicotine in mice: Genetic and pharmacological approaches - Varani, Andrés Pablo (2014)
Previous studies from our laboratory showed that anxiety-related responses induced by nicotine (NIC), measured by the elevated plus maze, were abolished by 2-OH-saclofen (GABAB receptor antagonist) (1 mg/kg; ip) or the lack of GABAB receptors (GABAB1 knockout mice). Based on these behavioral data, the aims of the present study were: 1) to evaluate the possible neurochemical changes (dopamine, DA, serotonin, 5-HT, 3,4-dihydroxyphenyl acetic acid, DOPAC, 5-hydroxyindoleacetic acid, 5-HIAA and noradrenaline, NA) and the c-Fos expression induced by the anxiolytic (0.05 mg/kg) or anxiogenic (0.8 mg/kg) doses of NIC in the dorsal raphe (DRN) and lateral septal (LSN) nucleus; 2) to study the possible involvement of GABAB receptors on the neurochemical alterations and c-Fos expression induced by NIC (0.05 and 0.8 mg/kg), using both pharmacological (2-OH-saclofen) and genetic (mice GABAB1 knockout) approaches. The results revealed that in wild-type mice, NIC (0.05 mg/kg) increased the concentration of 5-HT and 5-HIAA (p<0.05) in the DRN, and NIC (0.8 mg/kg) increased the levels of 5-HT (p<0.01) and NA (p<0.05) in the LSN. Additionally, 2-OH-saclofen pretreatment (1 mg/kg, ip) or the lack of GABAB receptors abolished these neurochemical changes induced by NIC (p<0.01, p<0.05, respectively). On the other hand, NIC 0.05 and 0.8 mg/kg increased (p<0.01) the c-Fos expression in the DRN and LSN respectively, in wild-type mice. In addition, 2-OH-saclofen pretreatment (1 mg/kg, ip) or the lack of GABAB receptors prevented the c-Fos alterations induced by NIC (p<0.01). In summary, both approaches show that GABAB receptors would participate in the modulation of anxiolytic- and anxiogenic-like responses induced by NIC, suggesting the potential therapeutic target of these receptors for the tobacco addiction treatment.